GEOCHRONOLOGY, DISTRIBUTION, AND ICE VOLUME ON THE EARTH DURING THE LAST GLACIAL MAXIMUM: INFERENCES FROM NEW DATA - Velichko A.A.; Kononov Yu.M.; Faustova M.A. (My University, 2000)
The evaluated area and volume of ice sheets on the Earth during the Last Glacial Maximum (18-20 thousand years ago, oxygen isotope stage 2) are adjusted to the most recent data and our subglobal to global paleoglaciological reconstructions published between 1986 and 1997. In the West Eurasian Arctic sector (Svalbard and Franz Josef Land), the compensation uplift rate, calculated on the basis of radiocarbon dating of risen marine terraces, is considerably lower than that estimated using the model of an ice sheet stretched over the whole Barents Sea shelf. From the viewpoint of isostasy and new radiocarbon dates, according to which sediments left by the ice sheet of the Kara Sea are older than 40 ka, the idea suggesting a solid ice mass that existed in this region appears to be invalid. Glaciation in the Novaya Zemlya and Polar Urals was also autonomous. Glaciers in mountain valleys were typical of Taimyr and northeastern Siberia. Data on the western hemisphere again suggest a limited extent of glaciation in high latitudes, e.g., in the Canadian Arctic Archipelago. At the same time, ice sheets were most extensive in North America as compared to all others in the northern hemisphere. Outside the Antarctic continent, glaciation in the southern hemisphere was not intense; and limited ice sheets were mainly characteristic of southern South America and New Zealand. The total area of ice sheets during the Last Glacial Maximum was 36 million km2 and progressively decreased to 9600 thousand km2 about 13 ka ago and to 4700 thousand km2 about 10 ka years ago.